Acceleration and transport of relativistic electrons in the jets of the microquasar SS 433 - Olivera-Nieto, Laura; Reville, Brian; Hinton, Jim; Tsirou, Michelle (Science, 2024)
SS 433 is a microquasar, a stellar binary system that launches collimated relativistic jets. We observed SS 433 in gamma rays using the High Energy Stereoscopic System (H.E.S.S.) and found an energy-dependent shift in the apparent position of the gamma-ray emission from the parsec-scale jets. These observations trace the energetic electron population and indicate that inverse Compton scattering is the emission mechanism of the gamma rays. Our modeling of the energy-dependent gamma-ray morphology constrains the location of particle acceleration and requires an abrupt deceleration of the jet flow. We infer the presence of shocks on either side of the binary system, at distances of 25 to 30 parsecs, and that self-collimation of the precessing jets forms the shocks, which then efficiently accelerate electrons.
CRIS-Team Scopus Importer:2024-02-15